The Application of Active Learning Approach to Develop Academic Achievement on an Online Measurement and Evaluation in Elementary Education in MER3006 Course for Undergraduates of Faculty of Education, Ramkhamhaeng University - Hitakowit, Sirirat (Interdisciplinary Academic and Research Journal, 2023)
This research was the application of an active learning approach to develop academic achievement on online measurement and evaluation in elementary education in the MER3006 course. The application of the approach for online learning management is an effective method to develop students’ academic achievement during the Covid-19 pandemic. The objectives of this research were to 1) develop learning management based on an active learning approach on online measurement and evaluation in elementary education in MER3006 course for undergraduates of the Faculty of Education Ramkhamhaeng University to have a required efficiency of 80/80. 2) compare students’ academic achievements before and after learning with learning management based on an active learning approach on online measurement and evaluation in elementary education in the MER3006 course for undergraduates of the Faculty of Education Ramkhamhaeng University. 3) student satisfaction with learning management based on an active learning approach on online measurement and evaluation in elementary education in MER3006 course for undergraduates of the Faculty of Education Ramkhamhaeng University. Findings are as follows: (1) The learning management based on an active learning approach on online measurement and evaluation in elementary education satisfied the efficiency standard at 84.64/82.37 in consonance with criteria 80/80. (2) The student’s academic achievements after study with the learning management based on an active learning approach on online measurement and evaluation in elementary education were higher than the student’s academic achievements before the learning. (3) The student satisfaction with the learning management based on an active learning approach on online measurement and evaluation in elementary education in MER3006 was at a high level.